Medicinal benefits and scientific justification of Commiphora mukul (Muqil): A review - Bhat, Shabir Ahmad; Rather, Shameem Ahmad (Journal of Drug Delivery and Therapeutics, 2021)
Commiphora mukul (Muqil or Guggul), oleo-gum, has been in use for thousands of years as a medicine in Unani and Ayurvedic medicinal systems. It was primarily used for swellings, inflammation, piles, arthritis and urinary disorders. Among its various types Muqil-I-Arzaq, a gum, having reddish hue is considered to be the best form of Muqil for medicinal purposes. It has been revealed to inhibit the nuclear factor-kb, a regulator of inflammatory response, and act as a potent antagonist to the receptors of androgens, mineralocorticoides, and glucocorticoides. Muqil is a versatile herb with diverse medicinal benefits which demand scientific validation. A coherent review of properties, medicinal benefits, traditional uses and scientific studies of Muqil, along with the overall processes involved from collection to consumption is judiciously described in this paper. The aim of this review is to provide a base for multiple research works, validating Commiphora mukul in different chronic ailments.keywords:  Commiphora mukul, Inflammation, Muqil, Nuclear factor-KB, Unani